2022
DOI: 10.1002/adom.202200471
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Reflective Plasmonic Structural Colors from Nanoparticles and Cavity Resonances – the Cyan‐Magenta‐Yellow Approach

Abstract: the manifold advantages they have over pigmentary methods. Traditional modes of color generation are chemically unstable at high temperatures, subject to bleaching if exposed to intense UV illumination, difficult to dispose of or recycle due to toxic composition, and unsuitable for miniaturized imaging and display devices. [1] In favorable contrast to these methods, metasurfaces have shown to be more robust to chemical deterioration, [2] can deliver high spatial resolution [3] and are potentially more economic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
(55 reference statements)
0
8
0
Order By: Relevance
“…It has been reported that the plasmonic filed coupling of the MIM structure results from a combination of gapsurface plasmon resonance and Fabry-Perot-like resonance. [39][40][41] In such a MIMn plasmonic cavity, when the insulator thickness is very thin, gap-surface plasmon resonance is excited due to the strong near field coupling between the two metallic layers and the gap-surface plasmon resonance occupies an important position on the influence of the optical property. As the insulator thickness increases, near field coupling becomes weaker, leading to weakening of gap-surface plasmon resonance, and thus, the optical property is mainly dominated by Fabry-Perot-like resonance.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the plasmonic filed coupling of the MIM structure results from a combination of gapsurface plasmon resonance and Fabry-Perot-like resonance. [39][40][41] In such a MIMn plasmonic cavity, when the insulator thickness is very thin, gap-surface plasmon resonance is excited due to the strong near field coupling between the two metallic layers and the gap-surface plasmon resonance occupies an important position on the influence of the optical property. As the insulator thickness increases, near field coupling becomes weaker, leading to weakening of gap-surface plasmon resonance, and thus, the optical property is mainly dominated by Fabry-Perot-like resonance.…”
Section: Resultsmentioning
confidence: 99%
“…(a) Schematic of gap plasmonic structure based on aluminum nanorods (1), and achieving structural color pixels with a single nanostructure and black pixels by blending different nanostructures (2) [113] . (b) Process flow and structural schematic of large-scale preparation of Ag nanorod gap plasmonic structures using colloid lithography, along with samples and characteristics in CMY mode—cyan, magenta, and yellow (2) [114] .…”
Section: Static Structural Colorsmentioning
confidence: 99%
“…Blake et al . designed a subtractive color reflection structural color based on the gap plasmon mode [114] . They utilized a hole-mask colloidal lithography (HCL) method to fabricate the top-layer nanodisk structures, achieving a large-area preparation process for reflective cyan, magenta, and yellow (CMY) structural colors, as illustrated in Fig.…”
Section: Static Structural Colorsmentioning
confidence: 99%
“…On the other hand, colloidal lithography (CL) has been widely applied to prepare periodic two-dimensional nanosized patterns such as nanoholes, , nanodisks, and nanocones on various substrates in a large area . Further complicated hierarchical nanostructures such as silicon nanorings and nanotowers were fabricated by using multiple patterning CL. , Previously, we fabricated TiN nanoring broad-band absorbers using multiple patterning CL .…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Though TiN-based absorbers with various nanostructures such as nanohole, nanodisk, and nanoring have been fabricated, there is a limitation to fabricating these nanostructures in a large area due to electron beam lithography. 12,18−20 On the other hand, colloidal lithography (CL) has been widely applied to prepare periodic two-dimensional nanosized patterns such as nanoholes, 21,22 nanodisks, 23 and nanocones 24−26 on various substrates in a large area. 27 Further complicated hierarchical nanostructures such as silicon nanorings and nanotowers were fabricated by using multiple patterning CL.…”
Section: ■ Introductionmentioning
confidence: 99%